Better business grammar - Communication Briefing (Blackwood, N.J. : Communication Briefing, 1991)
This video offers dozens of tips you can use right away to avoid grammar usage errors that can ruin your chance to make a good first impression.
Copy available in DVD format
Keywords: Business writing; Commercial correspondence